Assessment of Serum Biochemical Indices of Albino Rats Induced with Naja nigricollis Venom and Treated with Parkia biglobosa Stem Bark - Keta, J.N. (UMYU Journal of Microbiology Research)
Assessments of Serum Biochemical Indices of Albino Rats induced with Naja nigricollis venom treated with Parkia biglobosa stem bark were conducted and evaluated. A total of 42 healthy adult Albino rats of both sexes and average weight 153 -275g were used for the experiment. The venom was collected in low light condition at ambient temperature by using a short acting general anesthesia (Halothane) and kept at 4oC. The rats were injected with venom at 0.04 mg followed by conventional anti venom (1 ml) and the plant extract were administered at different doses of 300, 500 and 700 mg/kg respectively. The animals were scarified, and 5ml of blood samples were collected from each rat within 24hrs and tested for ALP, ALT, AST, total protein and Albumin. The LD50 was determined using Lorke’s method and found to be greater than 500mg/kg per oral. The results showed increased and decreased in ALT, ALP and AST while total protein and Albumin were normal. The stem bark extract of Parkia biglobosaa can be said to possess anti-snake venom activity which neutralize the toxic effects of N. nigricollis venom. The potent Snake venom neutralizing capacity of this plant extract is recommended for therapeutic purpose in case of snake bite.